Assessing Calcium and Magnesium Nutritional Status With the Hair Median Derivatives Bioassay. (7th June 2021) - Momčilović, Berislav; Prejac, Juraj; Mimica, Ninoslav
Abstract: Objectives: Short-term biological indicator of urinary Mg and Ca excretion helps us to assess human body Mg and Ca nutritional status. In this study, we used the long-term biological indicator tissue of hair to assess Mg and Ca human body nutritional status. Methods: Hair Mg and Ca were analyzed in 1073 healthy white adult Caucasians [734 women (♀) and 339 men (♂)] consuming common mid-European diet, with the ICP MS. The log transformed data on hair magnesium and calcium were analyzed with median derivatives bioassay. Results: The median values (μg·g −1 ) were ♀Mg 137.2 and ♂Mg 47.1, and ♀Ca 1721.4 and ♂Ca 492.0, respectively. The linear (adequate) reference ranges of the sigmoid saturation curve for magnesium were ♀Mg 29.7–270.6 and ♂Mg 20.5–90.2, whereas these ranges for calcium were ♀Ca 487.7–4426.8 and ♂Ca 261.1–816.4. The magnesium to calcium (Mg/Ca) ratio in women appears fairly constant along the sigmoid linear segment range (about 0.067), and in difference to the constantly increasing Mg/Ca ratio in men - from 0.078 at the start of the linear segment to 0.096 at the median and 0.1105 before leveling at the top of the curve. Conclusions: Women tend to accumulate much more Ca in their hair than men. The results suggest how hair Mg concentration should not be below 29.7 and 20.5 or above 270.6 and 90.2 μg·g −1 in women and men, respectively. Similarly, Ca hair concentrations should be not below 487.7 and 261.1 and higher than 4456.8 and 816.4 in women and men, respectively. The possible health effects of the observed sex related metabolic difference between men and women remains to be elucidated. Funding Sources: The authors received no specific funding for this work.